Letter - Araquistain, Luis, 1886-1959
1940-11-18 013-0063-001 4, Warnborough Road Oxford, 18th November 1940 Sir Walter Citrine Dear Sir Walter, I thank you very much for the letter of the 16th November about your intervention on behalf of Largo Caballero and I hope that, in spite of the present relations between the two countries, something effective will be done. I hear that Nicolau D'Oliver, a former Republican minister, governor of the Banco de Espana and a high authority on classical Greek literature, is too in the hands of Franco, in the gaol of Monjuitch, Barcelona, and I am afraid that other Socialist members of the Cortes, Rodolfo Llopis, Pascual Tomas, Carlos Hernandez and Enrique de Francisco, have been trapped too with Caballero. They were in the South of France. Yours sincerely, Luis Araquistain 292/946/13/63(i)